Penerapan Model Project Based Learning untuk Meningkatkan Materi Pembagian di Kelas Iv Sd Muhammadiyah 11 Medan - Irandi Sitinjak; Karina Wanda (Syntax Literate, 2023)
Learning in schools requires effective strategies to ensure understanding of the material by students. One of the challenges faced in learning mathematics is understanding the concept of division, especially at the elementary school level. The purpose of this study was to examine the application of PBL model to improve division material in class IV SD Muhammadiyah 11 Medan. The research method used in this research is qualitative research method. Data collection techniques in this research include observation, interview and test. The data that has been collected is then analyzed thematically. The results showed that the application of Project Based Learning (PBL) model can improve students' understanding of division material. Students can better understand the concept of division in the abstract. The application of PBL model can also increase students' learning motivation. Students become more active and involved in the learning process. In addition, the application of PBL model can also improve students' critical thinking skills. Students can think more independently and solve problems in a creative way.